178 Application of cardiac mri to quantitatively assess myocardial damage in isoproterenol-induced heart failure. (5th June 2017) - Han, Xiao Xiao; Ellison, Georgina; Lythgoe, Mark F; Stuckey, Daniel J
Abstract : Introduction: Cardiovascular disease is the Number-1 cause-of-death globally with an estimation of 17.5 million deaths annually. Being one of the most active organs of the body, the heart is vulnerable to damage. Isoproterenol (ISO) injection into mice can induce a stress cardiomyopathy model similar to Takotsubo cardiomyopathy. Cardiac MRI permits the detection, visualisation, quantification, and progression-monitoring of cardiac defects non-invasively, making it useful for monitoring stress cardiomyopathy. In this study, we used MRI to study the effects of ISO injection on cardiac structure and function in both immune-competent and immune-deficient mice. Methods and Materials: 12 week old C57B6 (n=14) and immunocompromised NOD-SCID mice (n=18) were assigned to Control and ISO Group with 0.9% saline or 1 mg/kg ISO administered daily for 7 days by i.p. injection. At 7 days imaging was performed using a 9.4T MRI system and 38 mm quadrature birdcage RF coil. Cardiac and respiratory gated cine-MRI was performed in the true short-axis orientation and covered the whole left ventricle. LGE-MRI was performed 20 min after i.p. injection of 0.5 mmol/kg Gd-DTPA-BMA using a multi-slice inversion recovery sequence. Data were analysed in a blinded fashion using ImageJ. LGE-MRI images were thresholded to the full width at half maximum of enhanced regions to identify areas of signal enhancement. Results: ISO caused changes in: 1) cardiac function – increasing end diastolic and end systolic volumes while decreasing ejection fraction, 2) cardiac morphology – increasing the left ventricular mass resulting in hypertrophy (enlargement of the heart), and 3) cardiac fibrosis – apex of the heart being the most vulnerable. A differential-distribution of fibrosis-severity across the heart has also been detected. Discussion: In agreement with initial hypothesis, there was a differed-response between Immunocompetent and Immunocompromised subgroups: the Immunocompetent showed a trend towards cardiac hypertrophy, whereas the Immunocompromised were more vulnerable to fibrosis. This cardioprotective role of the immune system could be due to CXCR4 signalling that is also implicated in cancer-metastasis, stem-cell-migration, angiogenesis, and haematopoiesis, which we will follow up. Conclusion: ISO-murine-disease-model has been established and characterised to study myocardial damage, with cardiac function, morphology, and damage in the form of fibrosis detected, visualised, and quantitatively assessed using cardiac MRI. ISO caused changes in cardiac function, morphology, and fibrosis. There was also a differential-distribution of fibrosis-severity across the heart as shown visually by high-resolution sequential MRI images.